Citation matters: mobilizing the politics of citation toward a practice of 'conscientious engagement'. Issue 7 (3rd July 2017) - Mott, Carrie; Cockayne, Daniel
Abstract: An increasing amount of scholarship in critical, feminist, and anti-racist geographies has recently focused self-reflexively on the topics of exclusion and discrimination within the discipline itself. In this article we contribute to this literature by considering citation as a problematic technology that contributes to the reproduction of the white heteromasculinity of geographical thought and scholarship, despite advances toward more inclusivity in the discipline in recent decades. Yet we also suggest, against citation counting and other related neoliberal technologies that imprecisely approximate measures of impact, influence, and academic excellence, citation thought conscientiously can also be a feminist and anti-racist technology of resistance that demonstrates engagement with those authors and voices we want to carry forward. We argue for a conscientious engagement with the politics of citation as a geographical practice that is mindful of how citational practices can be a tool for either the reification of, or resistance to, unethical hierarchies of knowledge production. We offer practical and conceptual reasons for carefully thinking through the role of citation as a performative embodiment of the reproduction of geographical thought.